Joyful Learning dalam Pembelajaran Matematika: Studi Literatur - Nabila, Intan; Nur Santoso, Khanza Maritza; Kusno (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Mathematics learning often causes anxiety and is perceived as difficult by students, which leads to low learning outcomes and reduced motivation. This highlights the need for an approach that can create a more enjoyable and meaningful learning atmosphere. One approach believed to be effective is Joyful Learning, which emphasizes active, interactive, and emotionally positive learning experiences. However, in-depth studies on the outcomes of Joyful Learning implementation in mathematics education are still limited. This study is a literature review that aims to analyze various research findings related to the implementation of Joyful Learning in mathematics learning. The data were obtained from 20 selected articles that met specific inclusion criteria and were published between 2015 and 2025. The data analysis technique used is content analysis with a descriptive qualitative approach, by identifying patterns, trends, strategies, and the impact of Joyful Learning implementation in mathematics education. The analysis results show that Joyful Learning has a positive impact both cognitively and affectively, such as improving learning outcomes, conceptual understanding, motivation, interest, active participation, and students’ positive attitudes toward mathematics. The recommendation of this study is to create more effective and enjoyable mathematics learning experiences.